Mathematical Modeling of Thin‐Layer Drying Kinetics of Cape Gooseberry (Physalis peruviana L.). Issue 2 (4th October 2012) - Vega‐Gálvez, Antonio; Puente‐Díaz, Luis; Lemus‐Mondaca, Roberto; Miranda, Margarita; Torres, María José
<x xml:space="preserve">Abstract</x> Abstract Drying kinetics of Cape gooseberry was studied and modeled during processing at four temperatures (60, 70, 80 and 90C). Desorption isotherm was obtained at 40C giving a monolayer moisture content of 0.086 g water/g d.m. Experimental drying curves showed that drying process took place only in the falling rate period. Several thin‐layer drying models available in the literature were evaluated based on statistical tests as sum squared error (SSE), chi‐square (χ2) and determination coefficient (R2). Effective moisture diffusivity of Cape gooseberry was in the range of 4.67–14.9 × 10−10 m2/s. A value of 38.78 kJ/mol was determined as activation energy. When comparing the experimental with predicted moisture values, the Midilli–Kucuk model was found to give the best fit quality (SSE < 0.001, χ2 < 0.001, R2 > 0.99), showing this equation to predict very accurately the drying time of Cape gooseberry under the operating conditions studied. Practical Applications Demand for natural and healthy fruit and vegetable products with extended shelf life has urged the dehydrated food industry to look for raw materials of desirable nutritional and functional properties. Cape gooseberry, with its highly nutritional composition and its content of biologically active health‐promoting components, is therefore an excellent fruit raw material for the dehydrated food industry. Drying has the potential to deliver safe food products through enzyme inactivation and microbe destruction. Therefore, modeling of drying kinetics, as well as acquiring data on desorption isotherm or diffusion coefficient, is needed by the industry to manage efficiently dehydration techniques and avoid energy misuse. This could serve to demonstrate the environmental consciousness of the food processing industry, greatly appreciated by consumers.